MORTALITY OF TROPICAL FOREST TREE SEEDLINGS UNDER WATER AND SALT STRESS CONDITIONS - SACHAN, SHEPHALI; Jain, Avinash (Journal of Plant Stress Physiology, 2017)
Mortality of selected tropical forest tree species seedlings viz. Tectona grandis, Pongamia pinnata, Dalbergia latifolia and Gmelina arborea were tested under water and salt stress conditions for 4 months under nursery stage. Water stress included moderate and severe waterlogging & moderate and severe drought conditions. The salt stress in the soil was maintained to 4, 8 and 12 ds/m. Pot culture experiments with twenty treatment combinations following RBD factorial design were conducted in TFRI Jabalpur nursery. The water equivalent to the field capacity of the soil was provided to the seedlings to maintain waterlogging. The drought condition in polybags was maintained according to Permanent Wilting point (PWP), which was calculated on the basis of Cumulative Pan Evaporation (CPE) values measured through Open Pan Evaporimeter. Mortality of seedlings of the species under study increased with the increase in salt concentration from 4 to 12 ds/m. Gmelina arborea shown 100% mortality in 4ds/m, 8ds/m and 12ds/m concentration of salt. Cumulative effect of salt and waterlogging & salt and drought was found to be more prominent in Gmelina arborea as compare to other three species. Tectona grandis was found to be more tolerable to waterlogged followed by drought conditions. Â Waterlogging conditions observed to be excellent for Pongamia pinnata seedlings plantation shown 0% mortality. As a whole, the mortality of seedlings due to water and salt stress was found in the order Dalbergia latifolia (90.95%) > Gmelina arborea (82.50%) > Tectona grandis (74%) > Pongamia pinnata (35.56%).Â